Perhitungan efektivitas kondensor unit 2 di PLTU pelabuhan tarahan 2x8 MW - Sulistiyo, Eko; Ahnaf, Nadhif Zhaher; Ridwan, Muhammad (Jurnal Teknik Mesin Indonesia, 2024)
The condenser plays an important role in cooling the steam coming out of the turbine and turning it into condensate water again. However, there are several factors that can influence the effectiveness of the condenser, such as the NTU (Number of Transfer Unit) value, vacuum pressure and cooling water temperature, so they can have a significant impact on condenser performance and the overall working efficiency of the PLTU. This research was carried out at the Tarahan Harbor 2x8 MW PLTU. The aim of this research was to determine the influence and correlation of the NTU (Number of Transfer Units), vacuum pressure, and inlet cooling water temperature on the effectiveness of the condenser at the PLTU. This research method is quantitative, the research technique uses interviews, observation and documentation. The analysis used in this research uses multiple linear analysis. The research results show that the NTU (Number of Transfer Units) value has little influence on condenser effectiveness with an R-squared value of 0.24. Where the higher the NTU (Number of Transfer Units) value, the lower the condenser's effectiveness. Apart from that, vacuum pressure affects the effectiveness of the condenser with an R-squared value of 0.74. The higher the vacuum pressure (the more negative it is), the effectiveness of the condenser will increase. Meanwhile, the cooling water inlet temperature has no effect on the effectiveness of the condenser with an R-squared value of 0.09 because there are several parameters or other factors that influence the effectiveness of the condenser, such as cooling water circulation, pipe cleanliness, and the cleanliness of the condenser itself.